2021
DOI: 10.3390/app11167600
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spp. in Pigs Slaughtered in Small and Medium-Sized Abattoirs in Central Italy: Preliminary Results on Occurrence and Control Strategies

Abstract: Salmonella in pork is still a relevant safety issue in the EU, and specific regulations are in force to control this hazard in the meat chain, in a from farm to fork perspective. In Italy, the control is mainly based on official sampling at the slaughterhouse level. The prevalence of Salmonella, and isolated serovars, was investigated during a three-year survey in small and medium slaughterhouses in central Italy. A total of 400 pig carcasses samples were collected by official authorities during the observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In contrast, larger facilities, with higher automation and a faster processing speed due to a larger number of slaughtered pigs, may benefit from more systematic management practices, ensuring a higher level of hygiene control (Primavilla et al, 2023). Nevertheless, this findings deserves further confirmation since in previous study in Italy no correlation was observed among occurrence of Salmonella and the size of the slaughterhouses (Primavilla et al, 2021).…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, larger facilities, with higher automation and a faster processing speed due to a larger number of slaughtered pigs, may benefit from more systematic management practices, ensuring a higher level of hygiene control (Primavilla et al, 2023). Nevertheless, this findings deserves further confirmation since in previous study in Italy no correlation was observed among occurrence of Salmonella and the size of the slaughterhouses (Primavilla et al, 2021).…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, cross contamination could also occur when other animals, especially pigs, are slaughtered in the same GHE, as they are reported to have a higher prevalence of Salmonella spp. on carcass surfaces than wild boars [58,59]. This should be considered in epidemiological studies performed by sampling carcass swabs or meat cuts.…”
Section: Discussionmentioning
confidence: 99%
“…prevalence in EU countries with specific national guarantee plans; for example, for Denmark and Sweden, where Salmonella spp. prevalence has dropped to nearly zero (Primavilla et al., 2021). The results of the default risk profile ( Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%